Men at work? Debating shifting gender divisions of care. Issue 1 (March 2017) - Boyer, Kate; Dermott, Esther; James, Al; MacLeavy, Julie
In response to four commentaries on our paper 'Regendering care in the aftermath of recession?', we extend our discussion of the ongoing knowledge gap that prevails around shifting patterns of male work/care. Recognizing the spatial limits of extant theories of male primary caregiving, we discuss first the need to attend to the variegated landscapes of male caregiving across the globe. Likewise, the theoretical stakes of expanding the focus of 'mainstream' analysis to take account of the situated experiences and knowledges of men and women in countries of the global South. We then consider the subjects of our research inquiry (the 'who' of contemporary fathering) and how different definitions of male primary caregivers may reveal or conceal patterns and shifts in male caregiving practices. Lastly we consider questions of scale and research methodology. Although our paper employs a national-level analysis, we fully endorse the use of alternative scalar lenses and underline the need to analyse male care within the context of multiscalar and interacting sites of normative change: from nation state, to community, to home, to the body.